Against depth: the reception of Roland Barthes and Alain Robbe-Grillet in minimal sensitivity - Santana Pérez, Sandra (Escritura e Imagen, 2019)
The present article offers a contextualized study of Roland Barthes’s reception in the American artistic field: from the publication of his first writings about Alain Robbe-Grillet at the end of the 50s until the popularization of his theories with the essay «The Death of the Author» in 1967. Some key terms (like «shallowness», «literalism» or «objecthood») are proved to be common to the Barthes and Robbe-Grillet’s discourses and those of the minimal art.